The Effect of Discovery Learning Method and Motivation on the Writing Ability of Students in the Tenth Grade of SMA Negeri 20 Palembang - Suraidah, Suraidah; Tahrun, Tahrun; Yukamana, Hanny (Journal of Social Work and Science Education, 2023)
The purpose of this research was to assess the effect of Discovery Learning Method and motivation of writing ability in descriptive text especially writing about pet animal at the tenth grade of SMAN 20 Palembang. As many as 72 students took the sample. The sampling technique was the tenth grade of students at the SMAN 20 Palembang, the data collection was done by distributing questionnaires on a 5-point likert scale with 15 statements. The analysis method used the normality test, homogeneity test and the two-way ANOVA. The researcher used the two-way ANOVA, to know the interaction effect between independent variable and dependent variable. The results showed that motivation between the experimental group and control group had a difference. The students wrote the descriptive text, they were taught using the discovery learning Method and had a significant increase on students’ writing ability in traditional teaching.